Analysis of The Effect of Service Income and Work Stress on Doctors' Organizational Commitment and Job Satisfaction as an Intervening Variable at dr. H. Jusuf SK of North Kalimantan Province - Nugroho Setyowardoyo; Kabul Wahyu Utomo; Nurul Hidayat (Green Publisher Indonesia, 2025)
This study aims to analyze the obstacles to the implementation of the JKN program related to patient admission, medical data processing, reporting, and funding at RSU Murni Teguh Medan. The formulation of the identified problems includes obstacles in the admission of BPJS Kesehatan patients, both outpatient and inpatient, medical data processing, reporting, and funding of BPJS patients. The purpose of the research specifically includes the analysis of the BPJS patient admission process and the obstacles faced, medical data processing, internal and external reporting, as well as the BPJS patient funding process, including the evaluation of obstacles based on the 6M elements (man, materials, machines, methods, markets, money). This research is expected to provide benefits, both for researchers as scientific experience, for hospitals to establish efficient service development strategies to improve service quality and patient satisfaction, and for BPJS Kesehatan to improve service quality, adjust policies to the development of science, and optimize service digitalization.